Glycoside hydrolase stabilization of transition state charge: new directions for inhibitor design. Issue 38 (21st September 2020) - Ren, Weiwu; Farren-Dai, Marco; Sannikova, Natalia; Świderek, Katarzyna; Wang, Yang; Akintola, Oluwafemi; Britton, Robert; Moliner, Vicent; Bennet, Andrew J.
Abstract : Positive charge stabilized on remote C5-allylic center with catalysis occurring via a loose SN 2 transition state. Abstract : Carbasugars are structural mimics of naturally occurring carbohydrates that can interact with and inhibit enzymes involved in carbohydrate processing. In particular, carbasugars have attracted attention as inhibitors of glycoside hydrolases (GHs) and as therapeutic leads in several disease areas. However, it is unclear how the carbasugars are recognized and processed by GHs. Here, we report the synthesis of three carbasugar isotopologues and provide a detailed transition state (TS) analysis for the formation of the initial GH-carbasugar covalent intermediate, as well as for hydrolysis of this intermediate, using a combination of experimentally measured kinetic isotope effects and hybrid QM/MM calculations. We find that the α-galactosidase from Thermotoga maritima effectively stabilizes TS charge development on a remote C5-allylic center acting in concert with the reacting carbasugar, and catalysis proceeds via an exploded, or loose, SN 2 transition state with no discrete enzyme-bound cationic intermediate. We conclude that, in complement to what we know about the TS structures of enzyme-natural substrate complexes, knowledge of the TS structures of enzymes reacting with non-natural carbasugar substrates shows that GHs can stabilize a wider range of positively charged TS structures than previously thought. Furthermore, this enhanced understanding will enable the design of new carbasugar GH transition state analogues to be used as, for example, chemical biology tools and pharmaceutical lead compounds.